2012
DOI: 10.1111/j.1360-0443.2012.03846.x
|View full text |Cite
|
Sign up to set email alerts
|

Childhood and adolescent psychopathology and subsequent tobacco smoking in young adults: findings from an Australian birth cohort

Abstract: Word count: 3159This is a post-print version of the following article: Fischer, Jane A., Najman, Jackob M., Williams, Gail M. and Clavarino, Alexandra M. Participants: A five, 14 and 21 years follow-up of children whose mother's were recruited into the MUSP birth cohort study at their first antenatal visit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 46 publications
(78 reference statements)
4
37
0
Order By: Relevance
“…The finding that young adult females have poorer mental health as a consequence of smoking and that smoking subsequently reduces mental health has been recently reported among an Australian sample (Leung et al, 2012). The majority of studies reporting associations between symptoms of adolescent psychopathology and substance use typically find stronger relationships with externalizing rather than internalizing problems (Fischer et al, 2012). The present study suggests that individuals with internalizing problems, including depressive symptoms, are at risk of using substances as well, even after controlling for the development of these problems over time and after taking into account a variety of important covariates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The finding that young adult females have poorer mental health as a consequence of smoking and that smoking subsequently reduces mental health has been recently reported among an Australian sample (Leung et al, 2012). The majority of studies reporting associations between symptoms of adolescent psychopathology and substance use typically find stronger relationships with externalizing rather than internalizing problems (Fischer et al, 2012). The present study suggests that individuals with internalizing problems, including depressive symptoms, are at risk of using substances as well, even after controlling for the development of these problems over time and after taking into account a variety of important covariates.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies have examined how these two constructs influence each other (e.g., depressive symptoms) by controlling for concurrent or previous levels of the other construct (e.g., cigarette use) (Fischer et al, 2012; Low et al, 2012; Mickens et al, 2011). The exact unfolding of the co-occurrence between depressive symptoms and cigarette use during the transition from adolescence to adulthood may involve bidirectional effects (Bares & Andrade, 2012; Leung, Gartner, Hall, Lucke, & Dobson, 2012).…”
Section: Other Substance Usementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, evidence indicated that childhood psychopathology was associated with higher rates of early substance use and problem substance use (King et al, 2004). Externalizing disorders (e.g., conduct problems and ADHD) have been found to have the strongest impact on later tobacco use, and children displaying aggressive behavior at 5 years were more likely to consume tobacco 14 years later (though, surprisingly, no association was found between externalizing problems and a prediction of DSM-IV nicotine dependence at 21-year follow-up; Fischer et al, 2012). However, in general, children with an early onset of conduct problems (onset in preschool) and a high degree of continuity seemed to have a much more negative prognosis than children with a late onset (adolescence) (McMahon, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…However, in general, children with an early onset of conduct problems (onset in preschool) and a high degree of continuity seemed to have a much more negative prognosis than children with a late onset (adolescence) (McMahon, 1999). In conclusion, psychopathology such as externalizing problems in childhood and adolescence appeared to predict unfavorable behaviors such as tobacco consumption in later life (Fischer et al, 2012). …”
Section: Introductionmentioning
confidence: 99%